Impact satisfaction factors of ecotourism for sustainable tourism business and management - Abdullah, N.; Kalai Arasi, M.; Thavamalar, R.; Suhaimi Salleh (Primrose Hall Publishing Group, 2020)
In almost all real-world problems, consideration of multiple-criteria decisions requires the decision maker to make constructive decisions to obtain the desirable outcomes. A multiple-criteria decision making tool is the Analytic Hierarchy Process (AHP) which is frequently used in most applications involving decision making. Since Sabah is well known for its natural and rich resources, ecotourism has a significant potential to enhance the tourism industry. This paper aims to determine the satisfaction factors of tourists visiting Sabah and specifically in the ecotourism industry. The four-step modelling procedure for a decision model using AHP is introduced. It includes the pairwise comparison table, building of the normalised matrix, weightage determination, and finally, the consistency ratio of the overall main criteria. The ranking of the main and sub-criteria are then made so that the best main and sub-criteria related to tourist satisfaction are identified. The results showed that the top criteria preferred by tourists for eco-tourism is safety, followed by benefits, activities, services and finally destination. The most strongly preferred sub-criteria for destination is 'interest', for benefit is 'relaxing and fulfilling', for activities is 'experiencing nature and beautiful scenery', for safety is 'concerned personal Safety and security', and for service is 'on time service to tourists'. All preferred factors have met the values of inconsistency of less than 0.1 (<0.1). Findings of these impact factors towards ecotourism may enhance further adventurous and physical challenges at Sabah ecotourism hotspots by introducing, increasing and developing more adventurous activities, inclusive of notified safety and security, which needs sustainable tourism management. In conclusion, tourists are said to be very satisfied with the ecotourism industry in Sabah as indicted in their great positive responses, hence creating more tourism businesses.